THE LEGAL FRAMEWORK OF NATIONAL SECURITY IN MONGOLIA AND AN ANALYTICAL ASSESSMENT - Nergui Bayartogtokh; Batbayar Batmunkh; Batbayar Dashzeveg (International Journal of Innovative Technologies in Social Science, 2025)
This article examines the legal framework for ensuring national security in Mongolia and provides an analytical assessment of its structure, governance effectiveness, and reform needs. Drawing on contemporary security studies and human security theory, the study conceptualizes national security as a multidimensional governance system encompassing individual, societal, and state security. Using doctrinal legal analysis, systems analysis, and normative evaluation, the article assesses the coherence between constitutional provisions, national security policy documents, and sectoral legislation.The findings indicate that while Mongolia’s national security legal framework is formally comprehensive, it remains functionally constrained by weak policy-law-implementation linkages, fragmented institutional responsibilities, and limited accountability mechanisms. In addition, emerging non-traditional security threats-including information insecurity, socio-economic vulnerability, and declining public trust-are insufficiently addressed within binding and enforceable legal norms. Human security principles, although present in strategic discourse, remain largely declarative rather than operationalized in law.The article argues that advancing a human-centered, adaptive, and accountable legal governance model is essential for strengthening national resilience. By focusing on Mongolia as a small state operating in a complex security environment, the study contributes to broader debates on national security governance and legal reform in transitional and developing contexts.